Effects of REM sleep restriction during pregnancy on rodent maternal behavior - Gabriel N. Pires; Sergio Tufik; Monica L. Andersen (Brazilian Journal of Psychiatry, 2015)
Objective:To evaluate the effects of sleep restriction during pregnancy on maternal care and maternal aggression in a rodent model.Methods:Twenty-three female Wistar rats were assigned to one of two groups: control (n=12) or sleep restriction (n=11) during the entire pregnancy. At the fifth postpartum day, the animals were subjected to the resident-intruder paradigm and to the pup retrieval test.Results:Sleep restriction during pregnancy had no direct effects on maternal care. Regarding aggressive behavior, defensive aggression was increased by sleep loss, with a lower responsiveness threshold to hostile environmental stimuli. Sleep deprivation during gestation also reduced self-grooming behavior.Conclusion:Taking increased self-grooming as a behavioral correlate of anxiety in rodents, this study provides evidence that lactating dams were in a condition of reduced anxiety. From an adaptive perspective, this pattern of stress response may function to ensure proper maternal behavior, thereby guaranteeing the survival and viability of the litter. Under a translational perspective, the present article confronts the importance of biological and adaptive features to rodent maternal behavior with the relevance of sociocultural factors to the human mother-infant relationship and to the onset of postpartum depression.